A Personal Touch: The Most Important Strategy for Recruiting Latino Research Participants - García, Alexandra A. (J Transcult Nurs, 2016)
People from non-White racial groups and other underserved populations, including Latinos, are frequently reluctant to participate in research. Yet their participation into research is foundational to producing information that researchers and health care providers need to address health disparities. The purpose of this article is to describe challenges we have encountered along with culturally relevant strategies we used in five research studies to recruit Mexican American participants from community settings, some of whom were also of low socioeconomic status. We found that the most effective recruitment strategies reflect the common cultural values of personalismo, simpátia, confianza, respeto, and familismo.